The Colombia reader : history, culture, politics - Farnsworth-Alvear, Ann, 1965-; Palacios, Marco; Gómez López, Ana María, 1981- (Latin America readers., 2017)
Containing over one hundred selections ranging from songs, artwork, and poetry, to journalism, oral history, and scholarship-most published in English for the first time-The Colombia Reader presents a rich and multi-layered account of this complex nation from the colonial era to the present.